The Political Conditions of Transoxiana in the Islamic Era up to the Establishment of the Safavid Rule - Hamid Hajian-poor (تاریخ اسلام)
This research deals with the political conditions of Transoxiana in the beginning centuries of Islamic era up until the establishment of the Safavid dynasty in Iran. The rise of independent and semi-independent local states in the eastern half of the Iranian Plateau greatly helped the establishment of a united government by the Safavid dynasty in Iran. On the other hand, the political developments in Transoxiana helped the rise of the Timurid and shortly after the Uzbek power in the area. Internal developments plus the political and religious policies of the Timurids and the Uzbeks and their ideological and political confrontation with the Safavids had an enormous influence on the events in the 9th and 10th centuries A.H. lunar/ 15th and 16th centuries C.E.